Versäumte Aktualität - Immanuel Kants »Zum ewigen Frieden« - Jähner, Uli (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1997)
Kant's small political essay sketches the foundations and maxims of a global, civil republican legal status - between citizens and states and between the states themselves. Reading it today means encountering surprises among all the familiarities of a classical political text: The power of persuasion and anticipation in a historically alienated text of rational law which seems to have its topicality consistently consigned to oblivion.